A Confissão De Lúcio, De Mário De Sá-Carneiro: O Feminino, O Duplo E A Criação Ficcional - SILVA, Karla Jakeline Batista Da (Universidade Federal do Tocantins, 2023)
This article intends to present the work of Mário de Sá Carneiro, entitled "The Confession of Lucius", which portrays the love triangle between Ricardo-Marta-Lúcio. It is an untraceable story of Lucius' confession. Being a novel that has aspects of Modernism and embraces the Decadentista movement by the theme portrayed, it presents a writing of easy understanding breaking with tradition by expressing the homo-heterosexuality of the characters of the nineteenth century, the conflict existing in the mind of Lucius between his psychological and the world, the real-unreal, dream or madness of the i-lyric. Among the subjects addressed in the narrative are the duplicity of the characters and the hallucination Marta-Ricardo and Lúcio, the identity or otherness of Mário de Sá Carneiro with Lucius, the autobiographical relationship with his fictional work. Thus, the present work intends to analyze the work of Sá-Carneiro from the literary perspective observing aspects such as the double, the fictional creation and the representation of the feminine, in which the research methodology adopted was based on the theoretical perspective.